Manual on environmental law enforcement in coastal and marine areas (DENR, 2013)
"The manual aims to provide coastal and marine law enforcers on field with an accessible and concise sourcebook of environmental law violation in coastal and marine areas, procedures for arrest, search, seizure and case filing, and common cases on coastal and marine law enforcement"--Introduction.